The cranial morphology of Phrynomerus annectens Werner, with references to the systematic position of the Phrynomerinae (Microhylidae) - Immelman, D. J.(Daniel Johannes) (Stellenbosch : Stellenbosch University, 2012)
Full text to be digitised and attached to bibliographic record.